Promosi Wisata Gastronomi: Keunikan Daya Tarik Kuliner dan Cerita di Baliknya - Ayu Nurwitasari; Vanessa Gaffar; Lili Adi Wibowo; Mokh Adib Sultan (Society, 2024)
This study aims to identify and analyze the critical success factors for promoting gastronomic tourism, focusing on the role of local culinary attractions and the compelling power of storytelling. A systematic literature review was conducted, utilizing databases such as Google Scholar to gather relevant publications from 2020 to 2022. Key terms like “gastronomy,” “tourism,” and “promotion” guided the search, and only high-quality articles published in reputable journals were included, resulting in twenty selected publications for analysis. The findings reveal that tourism-related factors are the most frequently mentioned in the literature, highlighting their significance in shaping the overall gastronomic tourism experience. Additionally, local cuisine and destination image were identified as crucial elements, emphasizing the need for a holistic approach to promotion strategies. This approach should integrate various aspects, including food, destination appeal, and positive imagery, to create compelling and memorable tourism experiences. The study concludes that an effective gastronomic tourism promotion strategy must integrate these critical success factors, with storytelling playing a key role in connecting tourists to a destination’s cultural and culinary heritage. This research contributes to the literature by comprehensively analyzing the essential elements in promoting gastronomic tourism. It offers insights for developing strategies that promote gastronomic tourism, preserve cultural heritage, support local economies, and create a deeper connection between tourists and their destinations.